Determination of the crystallite size and crystal structure of magnesium powder by x-ray diffraction - ISMAIL ISMAIL; RESI MULIANI; ZULFALINA ZULFALINA; SITI HAJAR SHEIKH MD FADZULLAH (Universitas Syiah Kuala, 2020)
Magnesium powder has become an important material in the development of science and technology such as alloy and hydrogen storage. In this work, the chemical composition, crystallite size, and crystal structure of the magnesium powder sample have been studied by using x-ray fluorescent and x-ray diffraction. The x-ray diffraction data of the magnesium powder sample was analyzed by using the Rietveld method to obtain the crystal structure. Our results show that the purity of our magnesium powder sample is 93.1%. Our sample has good crystallinity with the average crystallite size of 31 nm. The crystal structure is found to be a hexagonal closed-packed structure with the lattice constants of 3.2100 Å (a and b-axis) and 5.2107 Å (c-axis). Our result revealed that the lattice constant in the c-axis of magnesium powder is influenced by impurity. This finding suggests that the impurity can affect the crystal structure of a material in general.